AN ASSESSMENT OF TECHNOLOGY PENETRATION IN THE LIVES OF PEOPLE OF THE ALIGARH DISTRICT - Rana, Tejbir Singh; Sharma, Arti; Ratnu, Bharat (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The use of technology plays an important role in saving time, as well as contributing immensely to the quality of life. This research paper is based on a primary survey of the Aligarh district. The primary data was collected during field visit to assess technological penetration/uses in the different spheres of the lives of people. And how technological uses impacting their beliefs and lifestyle. The countries which have a good penetration of technology in lives of their citizens, are more productive compared to other countries with less technological penetration. Hence, this research paper tries to find out the level and accessibility of technology in the lives of people of the Aligarh district and how the use of technology by people contributes to improve their quality of life. A total of 400 samples were collected during a field visit to the district, and findings show very interesting results regarding the penetration/uses of technology in different groups of people. All these results of research findings are discussed subsequently in this paper.